Estimation of Measurement Uncertainty Using Top-Down and Bottom-Up Approaches for Accurate Content Determination of Meloxicam in Injectable Dosage Forms - Karpicarov, Dino; Mitrevska, Ivana; Apostolova, Paulina; Arev, Marija; Arsova Sarafinovska , Zorica; Darkovska Sarafimovska, Marija; Dražić, Branka; Tonic Ribarska, Jasmina; Gjorgjeska, Biljana (Archives of Pharmacy, 2025)
Measurement uncertainty plays a critical role in ensuring the reliability, accuracy, and regulatory compliance of analytical results in pharmaceutical quality control. This study presents a comprehensive comparison of the Top-down and Bottom-up approaches for estimating the uncertainty associated with the quantitative determination of Meloxicam in injectable dosage forms using a validated HPLC method. The Top-down approach, based on method validation data, yielded an expanded uncertainty of ±0.336 mg per injection, while the Bottom-up approach (incorporating uncertainties from volumetric equipment, reference standards, and molar mass) produced a broader value of ±0.646 mg per injection. The results highlight the complementary nature of both approaches and support the integration of their respective strengths to improve the robustness of uncertainty estimation. The proposed methodology is applicable to other methods within pharmaceutical quality control.